Konsep Desain Reaktor Termonuklir Fusi Tokamak Sizeable Sebagai Sumber Daya Pembangkit Listrik Tenaga Nuklir Dengan Pengamanan Cryogenic - Dheo Erfiansyah; Yusnita Rahayu; Eddy Hamdani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Some implications and research about tokamak as nuclear fusion reactor are examined. From the other researching about tokamak shown that this nuclear fusion reactor has been developed significantly in last 3 decade. In this research to determine new concept to recreate the tokamak with more safety tendencies. The step from this idea to make tokamak is calculate the nuclear fusion cylce energy (based on electron-volt), magnetic field needed (e.m.u), the equilibrium value of nuclear reaction (in electron-volt), temperature and heat conversion of the result from fusion reaction. Also, as the measurement of the tokamak, this study using sizeable value to determine radius of orbit, the coil, etc. From the conclusion this tokamak concept has estimate to produced high energy and high temperature. The tokamak projected to have >200MeV equilibrium energy value and converted to heat energy around 500°C - 600°C. Which use as the fuel flowed to the boiler as a device to produce steam. Then steam will set in motion the turbine.Keywords: Nuclear Fusion, Tokamak, Equilibrium, Deuterium, Cryogenic